1991
DOI: 10.2165/00003495-199142030-00007
|View full text |Cite
|
Sign up to set email alerts
|

Atenolol

Abstract: Atenolol is a selective beta 1-adrenoceptor antagonist with a duration of activity of at least 24 hours. The scope of therapeutic use of the drug has been expanded and become better defined since it was first reviewed in the Journal in 1979. Atenolol is effective and generally well tolerated in patients with all grades of hypertension. Data from comparative studies show that when administered orally, atenolol reduces blood pressure to a similar extent, and in a similar proportion of patients, as usual therapeu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(14 citation statements)
references
References 239 publications
0
14
0
Order By: Relevance
“…Overall it is not uncommon that atenolol concentrations exceed 1 μg/L in Sweden and throughout Europe, although there is substantial variation in inlet concentrations. These high inlet concentrations are likely caused by atenolol passing through the human body without being completely metabolized (Wadworth et al 1991; Vieno et al 2006). Based on a literature survey, Kasprzyk-Hordern et al (2007, 2008) concluded that atenolol was excreted up to approximately 50 % in unchanged form, whereas others report values as high as 90 % (Stockholm Vatten 2010).…”
Section: Resultsmentioning
confidence: 99%
“…Overall it is not uncommon that atenolol concentrations exceed 1 μg/L in Sweden and throughout Europe, although there is substantial variation in inlet concentrations. These high inlet concentrations are likely caused by atenolol passing through the human body without being completely metabolized (Wadworth et al 1991; Vieno et al 2006). Based on a literature survey, Kasprzyk-Hordern et al (2007, 2008) concluded that atenolol was excreted up to approximately 50 % in unchanged form, whereas others report values as high as 90 % (Stockholm Vatten 2010).…”
Section: Resultsmentioning
confidence: 99%
“…Its principal action is to inhibit calcium entry through voltage-gated transmembrane L-type channels, thus decreasing intercellular calcium concentration and inducing smooth muscle relaxation [8][9][10]. Atenolol is a beta 1-selective drug that binds to the beta-receptors and prevents the stimulation by catecholamine resulting in lowering of heart rate and of the systemic blood pressure [11]. Captopril is an angiotensin-converting enzyme (ACE) inhibitor used for the treatment of hypertension and some types of congestive heart failure.…”
Section: Introductionmentioning
confidence: 99%
“…β-blockers are exceptionally toxic and most have a narrow therapeutic range; i.e., the differences between the lowest therapeutic and the highest tolerable doses are small. [1][2][3] Hence, accurate methods for the measurement of ATN are of great importance in pharmaceutical research. Several methods have been reported for the determination of ATN, including UV spectrophotometry, 4,5 spectroflurometry 6 and capillary zone electrophoresis in plasma.…”
Section: Introductionmentioning
confidence: 99%